2015
DOI: 10.1080/02640414.2015.1004638
|View full text |Cite
|
Sign up to set email alerts
|

Validation of two accelerometers to determine mechanical loading of physical activities in children

Abstract: The purpose of this study was to assess the validity of accelerometers using force plates (i.e., ground reaction force (GRF)) during the performance of different tasks of daily physical activity in children. Thirteen children (10.1 (range 5.4-15.7) years, 3 girls) wore two accelerometers (ActiGraph GT3X+ (ACT), GENEA (GEN)) at the hip that provide raw acceleration signals at 100 Hz. Participants completed different tasks (walking, jogging, running, landings from boxes of different height, rope skipping, dancin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
35
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(38 citation statements)
references
References 26 publications
2
35
1
Order By: Relevance
“…This analysis showed that peak segmental accelerations, regardless of accelerometer location, were strongest related to CoM acceleration from the 10-50% of the stance phase. Peak segmental accelerations, which previously have been used to investigate whole-body mechanical loading in daily life activities 7,8 or as in this and previously studies to validate whole-body loading from bodyworn accelerometry 5,6 , can therefore describe only part of the loading the body's soft tissues is exposed to during foot-ground-contact. Trying to use peak segmental accelerations to understand whole-body mechanical loading during foot-ground-contact in team sport movements could therefore be misleading.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…This analysis showed that peak segmental accelerations, regardless of accelerometer location, were strongest related to CoM acceleration from the 10-50% of the stance phase. Peak segmental accelerations, which previously have been used to investigate whole-body mechanical loading in daily life activities 7,8 or as in this and previously studies to validate whole-body loading from bodyworn accelerometry 5,6 , can therefore describe only part of the loading the body's soft tissues is exposed to during foot-ground-contact. Trying to use peak segmental accelerations to understand whole-body mechanical loading during foot-ground-contact in team sport movements could therefore be misleading.…”
Section: Discussionmentioning
confidence: 97%
“…Accelerometers located at the hip have for example demonstrated an acceptable association with the external forces acting on the whole body, biomechanically expressed as the ground reaction forces (GRF), during daily life activities 7,8 . In addition accelerometers located at the hip and tibia have shown a strong association with GRF in vertical jumping 9,10 .…”
Section: Introductionmentioning
confidence: 99%
“…This study utilised a cross-sectional design which required participants to undertake a single testing session within a laboratory setting to determine the reliability and validity of accelerometers housed within IMUs in the assessment of FFC GRF measures for pace bowlers (Elvin et al, 2007;Meyer et al, 2015;Nedergaard et al, 2017;Tran et al, 2010;Wundersitz et al, 2013).…”
Section: Methodsmentioning
confidence: 99%
“…A total of 11 recreationally-trained males (age = 26.8 ± 2.2 years; mass = 86.6 ± 9.9 kg; height = 1.85 ± 0.05 m), who were proficient in the movements of cricket pace bowling were recruited for this study. The sample size was determined by a power analysis (α = 0.05, power = 0.95, effect size = 1.24, calculated sample size = 11) using the variance between vertical acceleration and GRF data during a 0.3 m drop landing task, collected via a hip mounted accelerometer and force plate, respectively (Meyer et al, 2015). Furthermore, the number of participants recruited for the investigation is similar to or exceeds that of previous studies which have assessed the reliability and validity of mircosensor mounted segment acceleration data as compared to GRF during dynamic movements (Elvin et al, 2007;McNamara et al, in press;McNamara et al, 2015;Meyer et al, 2015;Tran et al, 2010).…”
Section: Participantsmentioning
confidence: 99%
See 1 more Smart Citation